Effect of Harvesting Time on Antioxidant Activities and Nutritive Value of Artemisia lactiflora - อารีศรีสม ภาวิณี; ท้าวแก่นจันทร์ นรินทร์; สุทนต์ วาริน; โทณลักษณ์ เทิดศักดิ์; อารีศรีสม กอบลาภ (KKU Science Journal, 2018)
This research was to study the effect of harvesting time (30, 60 and 90 days) on antioxidant activities and nutritive value of Artemisia lactiflora. The experiment was carried out based on Completely Randomized Design (CRD) with three replications. The results showed that the harvesting time was given a significantly different on antioxidant activities when estimated by DPPH and ABTS methods. The DPPH and ABTS radical scavenging activities provided consistent results. Harvesting time at 30 and 60 days gave the highest of antioxidant activities. The percentage of DPPH inhibition were 11.91 ± 0.58 and 11.66 ± 0.52, respectively while the percentage of ABTS inhibition were 9.52 ± 0.43 and 9.64 ± 0.35, respectively. The results of the nutritive value of Artemisia lactiflora showed that moisture content, ash, fat, carbohydrate and energy were statistically different when harvested at different time. Harvesting time at 30 days provided the highest of moisture, fat and ash contents (10.93 ± 0.35, 0.67 ± 0.10 and 17.17 ± 0.30 g/100g DW, respectively). The value of carbohydrate and energy were highest at 90-day harvesting time which were 58.27 ± 1.79 g/100g DW and 309.15 ± 6.34 kcal/100g DW, respectively. Protein and crude fiber of Artemisia lactiflora were not significantly different at various harvesting time.